1996
DOI: 10.1002/mds.870110209
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy in Huntington's disease: Evidence in favour of the glutamate excitotoxic theory?

Abstract: The gene responsible for Huntington's disease (HD) has been located, but its action and the pathophysiology of HD remain unclear. Glutamate excitotoxicity may contribute to the striatal neurodegeneration seen in HD. We used localised proton magnetic resonance spectroscopy (MRS) of the brain to investigate five patients with early HD, one symptom-free gene carrier, and 14 healthy volunteers. Peak area ratios of choline-containing compounds (Cho), glutamine and glutamate (Glx), and N-acetyl moieties including N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
3
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 15 publications
2
57
3
4
Order By: Relevance
“…2,3,18,19 Increased diffusivity in these structures has also been previously reported. 7,8 These results are consistent with the known neuropathologic features of HD 20 and with other MR imaging and positron-emission tomography neuroimaging findings, such as decreased N-acetylaspartate concentration, 21 glucose metabolism, and dopamine-receptor binding, all pointing to a neurodegenerative process. 22 Reduced volume of the caudate nucleus and putamen and, in the case of the caudate, also altered diffusivity indicate that structural abnormalities are present in HD gene carriers long before the predicted onset of the clinical symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…2,3,18,19 Increased diffusivity in these structures has also been previously reported. 7,8 These results are consistent with the known neuropathologic features of HD 20 and with other MR imaging and positron-emission tomography neuroimaging findings, such as decreased N-acetylaspartate concentration, 21 glucose metabolism, and dopamine-receptor binding, all pointing to a neurodegenerative process. 22 Reduced volume of the caudate nucleus and putamen and, in the case of the caudate, also altered diffusivity indicate that structural abnormalities are present in HD gene carriers long before the predicted onset of the clinical symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…64 Preclinical studies have suggested that HD can be mimicked in animals with the intrastriatal injection of certain excitotoxins that activate the N-methyl-D-aspartate (NMDA) glutamate receptor, as well as by injection of toxins that block mitochondrial oxidative phosphorylation. 65,66 Similar to studies of bipolar disorder, 1 H MRS investigations of HD have observed both elevated Glx/Cr þ PCr and lactate in the basal ganglia of HD patients when compared to normal controls 64,67 In fact, a recent study by Jenkins et al 63 observed significantly increased levels of glutamine in a transgenic mouse model of HD, and described these results as 'evidence of a profound metabolic defect.' It is thus possible that similar MRS findings in bipolar subjects may indicate a similar pathology of excitotoxicity and mitochondrial dysfunction.…”
Section: Elevated Lactate In Bipolar Disordermentioning
confidence: 88%
“…8,9 An increased sensitivity to QA-induced excitotoxicity was observed in the striata of some symptomatic transgenic mice carrying expanded CAG repeats in the huntingtin gene. 10,11 The excitotoxicity hypothesis of HD has been corroborated by an imaging study showing disordered glutamate metabolism in the brain of HD patients, 12 and clinical trials showing reduced chorea in HD patients treated with an NMDA receptor antagonist amantadine. 13 We have found that lithium, the primary drug used to treat bipolar mood disorder, has robust neuroprotective effects against excitotoxicity mediated by NMDA receptors in cultured brain neurons, [14][15][16][17] and brain damage induced by focal ischemia in rats.…”
mentioning
confidence: 94%